Human Resource Capacity Development Based on Financial Literacy in Realizing the SDGs: A Study of MSMEs in Central Maluku - Maghfirah, Nurul; Simanjuntak, Pranatalindo; Christianto Leasiwal, Teddy; Manuhutu, Yerimias (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This study aims to examine the development of human resource capacity of Micro, Small, and Medium Enterprises (MSMEs) in Central Maluku Regency through a financial literacy approach as a strategy to support the achievement of the Sustainable Development Goals (SDGs). This study uses a quantitative approach with a survey method, with a stratified random sampling technique.This study maps the financial literacy status of MSMEs and analyzes its relationship to improving management capacity and business sustainability to support the achievement of the SDGs. The results show that low levels of financial literacy in human resources are a major obstacle to efficient business management and delay the achievement of national sustainable development goals. Therefore, strengthening human resource capacity based on financial literacy is essential as a strategic intervention that not only increases the competitiveness of MSMEs but also directly contributes to the achievement of SDGs indicators, particularly in the areas of financial inclusion, poverty reduction, and sustainable local economic growth